An Inca account of the Conquest of Peru - Yupangui, Diego de Castro, titu cussi, active 16th century (University Press of Colorado, 2005)
Available in English for the first time, An Inca Account of the Conquest of Peru is a firsthand account of the Spanish invasion, narrated in 1570 by Diego de Castro Titu Cusi Yupanqui - the penultimate ruler of the Inca dynasty - to a Spanish missionary and transcribed by a mestizo assistant. The resulting hybrid document offers an Inca perspective on the Spanish conquest of Peru, filtered through the monk and his scribe. Titu Cusi tells of his father's maltreatment at the hands of the conquerors; his father's ensuing military campaigns, withdrawal, and murder; and his own succession as ruler.